THE URGENCY OF USING DISTINCTIVE SIGNS AT MUARO JAMBI TEMPLE SITE: A REVIEW FROM THE INTERNATIONAL HUMANITARIAN LAW PERSPECTIVE - Akbar Kurnia Putra; Bernard Sipahutar; Budi Ardianto (Faculty of Law Universitas Lampung, 2020)
This article discusses the role of international law in the protection of the Muaro Jambi Temple site as a cultural place. In specific, the authors highlight the regulations to use distinctive signsfor historical and cultural propertyunder the International Humanitarian Law. Even though all Contracting Members should comply with the law, in reality, not all the rules are implemented, such as in Muaro Jambi Temple site.A site is a principal object that passes the historical value of human being as well as scientific information from generation to generation; therefore, is required protection. Using a normative juridical approach, the article analyses the basic problems for not applying distinctive signs at the Muaro Jambi Temple site.